Functional Abdominal Pain in Children - Ermaya, Yudith Setiati (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Functional abdominal pain (FAP), often affecting girls and those with mental health issues, is a prevalent pediatric disorder characterized by persistent symptoms without a clear identifiable organic pathology. The Rome IV Criteria classify it into subtypes, which have distinct symptoms and required tailored management approaches. Discussion: Subtypes classified by the Rome IV Criteria include irritable bowel syndrome (IBS), functional dyspepsia, abdominal migraine, and FAP - not otherwise specified (NOS). The pathophysiology involves gut hypersensitivity, hyperalgesia, genetic predispositions, and psychosocial triggers. Diagnosis relies on medical history, physical examination, the presence of alarm signs, and the characteristic of pain. Treatment strategies encompass dietary modifications, psychological interventions, pharmacology treatment including proton pump inhibitors, prokinetics, and antidepressants like amitriptyline. Conclusion: Recognizing the specific subtypes, as defined by the Rome IV Criteria, allows healthcare professionals to implement individualized care strategies for optimal outcomes.